Analisis Tindak Tutur Representatif pada Video Mengerti Akuntansi Tanpa Menghafal dalam Kanal YouTube Akuntan Tampan - Atiya Najal Aufa; Hikmatul Amelia; Rahma Safitri; Yolanda Pretty Nazhifa Hanun; Angelica Hexa Trinita Pandiangan; Asep Purwo Yudi Utomo; Rossi Galih Kesuma; Desy Rufaidah (Lembaga Pengembangan Kinerja Dosen, 2025)
With advancements in technology, communication has become easier and more effective, especially through digital media. In the context of education, videos serve as a valuable source of information. This study aims to analyze the use of representative speech acts in the video